A Dynamic Region Surging into the New Decade (Mongolian Journal of International Affairs, 2014)
No abstract available DOI: http://dx.doi.org/10.5564/mjia.v0i8-9.126 The Mongolian Journal of International Affairs; Number 8-9, 2002, Pages 24-35